The Role of Resilience and Readiness for Change in Employee Performance at Company X - Previa Sabilla Qolby; Kartika Nuradina; Fauzan Daffa; Prass Rendy (International Journal of Marketing & Human Resource Research, 2026)
Organizational change places employees under continuous pressure to adjust while maintaining effective work behavior. This study examined whether resilience and readiness for change predict individual work performance among employees of Company X, a healthcare service organization operating across 44 branches. A quantitative cross-sectional explanatory design was employed. From a population of 255 employees, 72 respondents were selected through simple random sampling. Data were collected using adapted versions of the Connor–Davidson Resilience Scale, the Readiness for Change Scale, and the Individual Work Performance Questionnaire. The data were analyzed using descriptive statistics and multiple linear regression. The results showed that resilience positively and significantly predicted individual work performance ((B = 0.233), (t = 2.603), (p = 0.011)). In contrast, readiness for change had a positive but statistically nonsignificant contribution ((B = 0.052), (t = 0.611), (p = 0.543)). The overall regression model was significant ((F = 6.057), (p = 0.004)) and explained 14.9% of the variance in individual work performance. These findings indicate that employees’ capacity to remain persistent, regulate pressure, and recover from workplace difficulties is more directly related to performance than their general preparedness to accept organizational change. The study highlights the importance of strengthening employee resilience while improving managerial support, communication, and employee involvement during organizational transitions.